Efficient acceleration of a dense plasma projectile to hyper velocities in the laser-induced cavity pressure acceleration scheme. (25th January 2018) - Badziak, J.; Krousky, E.; Marczak, J.; Parys, P.; Pisarczyk, T.; Rosiński, M.; Sarzynski, A.; Chodukowski, T.; Dostal, J.; Dudzak, R.; Kalinowska, Z.; Kucharik, M.; et al.
Abstract: The experimental study of the plasma projectile acceleration in the laser-induced cavity pressure acceleration (LICPA) scheme is reported. In the experiment performed at the kilojoule PALS laser facility, the parameters of the projectile were measured using interferometry, a streak camera and ion diagnostics, and the measurements were supported by two-dimensional hydrodynamic simulations. It is shown that in the LICPA accelerator with a 200-J laser driver, a 4-μg gold plasma projectile is accelerated to the velocity of 140 km/s with the energetic acceleration efficiency of 15–19% which is significantly higher than those achieved with the commonly used ablative acceleration and the highest among the ones measured so far for any projectiles accelerated to the velocities ≥100 km/s. This achievement opens the possibility of creation and investigation of high-energy-density matter states with the use of moderate-energy lasers and may also have an impact on the development of the impact ignition approach to inertial confinement fusion.